2019
DOI: 10.1155/2019/7124318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electroacupuncture on Reuptake of Serotonin via miRNA-16 Expression in a Rat Model of Depression

Abstract: The current study aimed to investigate the effects and mechanisms of electroacupuncture (EA) treatment applied to Bai hui (GV20) and Yin tang (GV29) acupoints (1 mA, 2 Hz, continuous wave, 20 minutes) for 28 days in a rat model of chronic unpredictable mild stress (CUMS) on reuptake of serotonin (5-hydroxytryptamine (5-HT)) and miRNA-16 levels in the hippocampus and serum. Rats were housed in individual cages, and CUMS was used to establish a rat model of depression. After EA treatment for 4 weeks, behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…One of the major brain areas where EA ameliorates depressive behaviors of animals is the hippocampus, in which several mechanisms have been confirmed, such as synaptic plasticity, neuroinflammation, and neurotransmitter upregulation [ 48 50 ]. However, whether and how autophagy participates in the regulation of EA on depression are unclear yet.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major brain areas where EA ameliorates depressive behaviors of animals is the hippocampus, in which several mechanisms have been confirmed, such as synaptic plasticity, neuroinflammation, and neurotransmitter upregulation [ 48 50 ]. However, whether and how autophagy participates in the regulation of EA on depression are unclear yet.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, miR-16 is able to bind the SERT messenger ( Table 2 ) and silence its expression in humans and animals ( Baudry et al, 2010 ; Moya et al, 2013 ; Song et al, 2015 ; Shao et al, 2018 ). The relationship between miR-16 and SERT is even modulated by pharmacological antidepressant treatment and also alternative treatments as the electroacupuncture; besides different responses according to the affected brain area, these treatments improve the level of depressive behaviors, suggesting a highly specific regulation ( Baudry et al, 2010 ; Zhao et al, 2019 ). SERT appears to be a key piece of regulation, as different miRNAs can modify its expression, as the mmu-miR-135 ( Issler et al, 2014 ), rno-miR-18a-5p, rno-miR-34a-5p, rno-miR-135a-5p, rno-miR-195-5p, rno-miR-320-3p, rno-miR-674-3p, and rno-miR-872-5p ( Zurawek et al, 2017 ).…”
Section: Serotonin: Role On Feeding Behavior Influences Of Els and mentioning
confidence: 99%
“…The 3′-UTR of BDNF was also targeted by miR-16, which mediates the action of the antidepressant fluoxetine by acting as a micromanager of hippocampal neurogenesis [ 122 ]. Most interestingly, numerous studies have shown that EA can not only inhibit the expression of miR-16 in the hippocampus [ 132 ] but also increase the levels of BDNF in the brains of depression model rats [ 126 130 ]. Therefore, acupuncture promoted synaptic plasticity via BDNF protein expression and regulated a few miRNAs that were found to target BDNF, which seem to play important roles in the development of depression.…”
Section: Discussionmentioning
confidence: 99%
“…The CUMS rat model was used, and EA was administered at acupoints GV20 and GV29. After the administration of EA, depression-like behaviours were improved, and high expression of miR-16 in the hippocampus was inhibited as well [ 132 ]. Regrettably, this study did not directly explore the relationship between EA regulation of BDNF and neural plasticity.…”
Section: Main Textmentioning
confidence: 99%